Karakteristik Layanan Bimbingan Penggunaan Sumber Referensi - Purwani Istiana (Perpustakaan Nasional, 2023)
Services provided by the library need to be evaluated by users to improve their quality. This study aimed to determine the characteristics of users and the use of guidance services using reference sources at the Library of the Faculty of Geography, Gadjah Mada University, in August 2020-December 2022. These characteristics include service users, guidance themes, and reference sources used in guidance services. The quantitative descriptive method is used to answer research questions. The study results show that users of this service are dominated by student users, lecturers and education staff. Students who use this service are predominantly doctoral (S3) students. The most needed guidance themes are indexing databases, e-journals, and e-books. The next theme is using several applications, accessing library websites, using academic profiles, accessing journal websites, how to get ISBNs, identification of journals, and instructions for preparing scientific papers. The most widely used reference sources in guidance services are indexing databases (Scopus, Sinta, Garuda, and Directory Open Access Journal) and e-journal databases. Guidance on the use of applications needed is Mendeley, Turnitin, Grammarly, and VOSviewer applications. Users of guidance services on the use of reference sources need specific and in-depth guidance on reference sources, research support applications, library websites, academic profiles to increase knowledge dissemination, access to journal websites to submit articles, how to get International Standard Book Numbers, identify journals so they do not trap in predatory journals as well as guidance on writing scientific papers.